Profiling Signal Transduction in Global Marine Biofilms - Wang, Ruojun; Zhang, Weipeng; Ding, Wei; Liang, Zhicong; Long, Lexin; Wong, Wai Chuen; Qian, Pei-Yuan (Frontiers in Microbiology, 2022)
Microbes use signal transduction systems in the processes of swarming motility, antibiotic resistance, virulence, conjugal plasmid transfer, and biofilm formation. However, the signal transduction systems in natural marine biofilms have hardly been profiled. Here we analyzed signal transduction genes in 101 marine biofilm and 91 seawater microbial metagenomes. The abundance of almost all signal transduction-related genes in biofilm microbial communities was significantly higher than that in seawater microbial communities, regardless of substrate types, locations, and durations for biofilm development. In addition, the dominant source microbes of signal transduction genes in marine biofilms were different from those in seawater samples. Co-occurrence network analysis on signal communication between microbes in marine biofilms and seawater microbial communities revealed potential inter-phyla interactions between microorganisms from marine biofilms and seawater. Moreover, phylogenetic tree construction and protein identity comparison displayed that proteins related to signal transductions from Red Sea biofilms were highly similar to those from Red Sea seawater microbial communities, revealing a possible biological basis of interspecies interactions between surface-associated and free-living microbial communities in a local marine environment. Our study revealed the special profile and enrichment of signal transduction systems in marine biofilms and suggested that marine biofilms participate in intercellular interactions of the local ecosystem where they were seeded.